2002
DOI: 10.1183/09031936.02.00025802
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding and 24-h monitoring for efficacy and safety of aerosolized Nacystelyn in cystic fibrosis

Abstract: The aim of the present studies was to investigate the tolerability and activity of a novel mucolytic drug, Nacystelyn (NAL), for the treatment of cystic fibrosis (CF) lung disease.In study 1, involving 10 CF patients, the main objective was to determine the tolerability and potential efficacy of a range of single doses of NAL in comparison to a placebo, in order to establish an optimal dose for further testing. On five consecutive scheduled treatment days, patients inhaled either from two (4 mg) to eight puffs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Mucolytic agents, such as N-acetylcysteine, [229] nacystelyn, [230] and gelsolin, [231] may be used to enhance particle transport. Mucolytics disentangle the cross-linked mucus network and reduce the viscoelasticity of mucus.…”
Section: Breaching Biological Barriers Other Than Skinmentioning
confidence: 99%
“…Mucolytic agents, such as N-acetylcysteine, [229] nacystelyn, [230] and gelsolin, [231] may be used to enhance particle transport. Mucolytics disentangle the cross-linked mucus network and reduce the viscoelasticity of mucus.…”
Section: Breaching Biological Barriers Other Than Skinmentioning
confidence: 99%
“…Clinical trials have demonstrated the safety of NAL in healthy adults, smokers, and people with CF [96,97]. In a multicenter phase 2 trial, a placebo-controlled, double-blinded, randomized trial lasting 24 weeks demonstrated an improvement in mucus viscoelasticity in expectorated sputum and decreased self-reported respiratory infections with NAL aerosol administration (8 or 16 mg bid).…”
Section: Nacystelynmentioning
confidence: 99%
“…9 At the same time, no adverse effects were observed in CF patients, even at a high dose of 24 mg given via inhaler. 10 Presently, multiple phase I and phase II clinical trials are being undertaken in Europe and USA to assess the efficacy of NAL treatment in CF patients. Studies conducted in humans have also indicated that NAL prevents respiratory outburst of peripheral blood polymorphonuclear cells, indicating that it may have potential in reducing damage to lungs caused by an active inflammatory response, 11 which could be of a potential benefit in the context of adenoviral vectormediated CF gene therapy.…”
mentioning
confidence: 99%